Developing antineoplastic agents that target peroxisomal enzymes: cytisine-linked isoflavonoids as inhibitors of hydroxysteroid 17-beta-dehydrogenase-4 (HSD17B4). Issue 36 (4th September 2017) - Frasinyuk, Mykhaylo S.; Zhang, Wen; Wyrebek, Przemyslaw; Yu, Tianxin; Xu, Xuehe; Sviripa, Vitaliy M.; Bondarenko, Svitlana P.; Xie, Yanqi; Ngo, Huy X.; Morris, Andrew J.; Mohler, James L.; Fiandalo, Michael V.; et al.
Abstract : Cytisine-linked isoflavonoids (CLIFs) inhibit cancer cells by targeting the peroxisomal enzyme HSD17B4. Abstract : Cytisine-linked isoflavonoids (CLIFs) inhibited PC-3 prostate and LS174T colon cancer cell proliferation by inhibiting a peroxisomal bifunctional enzyme. A pull-down assay using a biologically active, biotin-modified CLIF identified the target of these agents as the bifunctional peroxisomal enzyme, hydroxysteroid 17β-dehydrogenase-4 (HSD17B4). Additional studies with truncated versions of HSD17B4 established that CLIFs specifically bind the C-terminus of HSD17B4 and selectively inhibited the enoyl CoA hydratase but not thed -3-hydroxyacyl CoA dehydrogenase activity. HSD17B4 was overexpressed in prostate and colon cancer tissues, knocking down HSD17B4 inhibited cancer cell proliferation, suggesting that HSD17B4 is a potential biomarker and drug target and that CLIFs are potential probes or therapeutic agents for these cancers.